Negative electrode material and method for preparing the same, and nickel-hydrogen secondary battery using the same

By forming a negative electrode material with a rare earth fluoride coating layer on the surface of the hydrogen storage alloy, the problem of poor stability of the hydrogen storage material in a high temperature environment is solved, and the multi-faceted performance of the nickel-hydrogen secondary battery is significantly improved.

CN115394991BActive Publication Date: 2025-03-18KINGSOFT TECH INNOVATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211126298.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-03-18
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The existing hydrogen storage materials have poor stability in high-temperature environments, especially in alkaline solutions, which are prone to elemental precipitation problems, resulting in poor circulation and high-temperature performance of nickel-hydrogen secondary batteries.

Method used

The negative electrode material combined with the hydrogen storage alloy and the cladding layer is used, the cladding content is ≥2 wt%, and consists of the general formula LnFx, which is a lanthanide element. The content of the cladding layer is adjusted by adjusting the ratio of the hydrogen storage alloy, Ln element salt and NH4F.

Benefits of technology

It significantly improves the physical and chemical stability of the negative electrode material in high temperature environments, and enhances the high-temperature stability, low-temperature discharge characteristics, charge and discharge cycle performance and rate charge and discharge performance of nickel-hydrogen secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115394991B_ABST
    Figure CN115394991B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode material, which comprises a hydrogen storage alloy and a coating layer arranged on the surface of the hydrogen storage alloy. Based on the mass of the negative electrode material, the content of the coating layer is ≥ 2wt%. The coating layer comprises a general formula LnF x The components shown in the figure, Ln is an element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc. The present invention also relates to a method for preparing the negative electrode material. The present invention also relates to a nickel-hydrogen secondary battery using the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nickel-hydrogen secondary batteries, and in particular to a negative electrode material, a method for preparing the negative electrode material, and a nickel-hydrogen secondary battery using the negative electrode material. Background Art

[0002] Nickel-metal hydride secondary batteries have the advantages of good low-temperature performance, resistance to overcharge / over-discharge, high safety, and environmental friendliness, and are widely used in portable electronic products, small power tools, and other fields. Existing nickel-metal hydride secondary batteries use nickel hydroxide as the positive electrode material and hydrogen storage materials as the negative electrode material. When charging, the positive nickel hydroxide is oxidized, and the negative electrode undergoes a water reduction reaction, and the released protons combine with the hydrogen storage material to form metal hydrides; when discharging, the process is just the opposite.

[0003] Hydrogen storage materials as negative electrode materials have a great influence on the performance of nickel-hydrogen batteries. Hydrogen storage materials that can absorb hydrogen and form hydrogen-absorbing alloys include: single substances that can undergo exothermic reactions with hydrogen, that is, metals that can form stable compounds with hydrogen (such as platinum group elements, lanthanide series elements and alkaline earth metal elements); or alloys formed by the above metals and other metals. The electrochemical hydrogen absorption and desorption reactions that occur in the electrodes formed by hydrogen storage materials during the charging and discharging process of nickel-hydrogen batteries are mainly related to the bulk properties of the hydrogen storage materials, the electrochemical reactions on the electrode surface, and the interface properties between the three phases of electrode / electrolyte / gas. Therefore, the performance of nickel-hydrogen secondary batteries can be improved by improving the performance of hydrogen storage materials (such as corrosion resistance, conductivity and electrocatalytic activity, etc.) through surface modification.

[0004] Conventional hydrogen storage materials are divided into the following categories (where A represents a metal element that can react with hydrogen to generate heat, and B represents other metal elements):

[0005] -AB5 type (such as LaNi5, CaNi5);

[0006] -AB2 type (such as MgZn2, ZrNi2);

[0007] -AB type (such as TiNi, TiTe);

[0008] -A2B type (such as Mg2Ni, Ca2Fe);

[0009] - Other types (such as atomic clusters).

[0010] The existing technical solutions to improve the performance of hydrogen storage materials are mainly alloy formula modification, doping, and surface treatment, aiming to achieve the following goals:

[0011] - Appropriately weaken the bonding strength between hydrogen storage materials and hydrogen, making the hydrogen absorption and desorption reactions relatively easy to carry out;

[0012] - Improve the relationship between the hydrogen absorption and desorption characteristics of hydrogen storage materials and the hydrogen pressure required for the reaction (equilibrium pressure, platform pressure), the range of the equilibrium region (platform region), the change of the equilibrium pressure during the hydrogen absorption process (flatness) and similar properties;

[0013] -Improve the physical and chemical stability of hydrogen storage materials.

[0014] Among them, the commonly used surface treatment methods of hydrogen storage materials mainly include: alkali treatment, acid treatment, fluorination treatment, surface coating, etc. By removing the surface oxide layer of the alloy, a nickel-rich sublayer or a modified surface layer with good corrosion resistance and conductivity is generated to improve the conductivity and corrosion resistance of the alloy. Among them, the commonly used doping methods of hydrogen storage materials mainly include: directly adding conductive materials (such as carbon nanotubes, acetylene black or graphene and other carbon materials) and / or materials containing rare earth elements (at least one element of La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc) in the reaction system by mechanical mixing to obtain a composite electrode material.

[0015] However, for the cycle and high temperature performance of hydrogen storage materials, although the above technical solutions can improve stability, they usually sacrifice other properties (such as capacity, high rate discharge, and low temperature performance). The problem of poor stability of hydrogen storage materials at high temperatures is particularly manifested in the precipitation of elements in hydrogen storage materials in high temperature alkaline solutions. It should be noted that, unless otherwise specified, the high temperature recorded in the present invention refers to a temperature ≥50°C. Summary of the invention

[0016] One of the purposes of the present invention is to provide a negative electrode material having excellent cycle performance and physical and chemical stability in a high temperature environment, and the high rate discharge performance and low temperature discharge performance of the negative electrode material at room temperature are improved.

[0017] Another object of the present invention is to provide a method for preparing the above-mentioned negative electrode material.

[0018] A further object of the present invention is to provide a secondary battery negative electrode with a very stable electrode reaction and a nickel-hydrogen secondary battery with improved charge and discharge cycle performance.

[0019] To achieve the above object, the present invention provides the following negative electrode material, which includes a hydrogen storage alloy and a coating layer arranged on the surface of the hydrogen storage alloy. Based on the mass of the negative electrode material, the content of the coating layer is ≥ 2wt%. The coating layer includes a general formula LnF xThe composition shown, wherein Ln is an element selected from lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), yttrium (Y) and scandium (Sc).

[0020] Hydrogen storage alloy is an alloy that can store and release hydrogen as a negative electrode active material. The content of hydrogen storage alloy in the negative electrode material will affect the capacity of the negative electrode material. From the perspective of taking into account both the capacity and stability of the negative electrode material, preferably, based on the mass of the negative electrode material, the content of the coating layer is 2-4wt%.

[0021] The coating layer has a thickness of 0.1-1000 nm. If the coating layer is less than 0.1 nm, the problem of incomplete coating of the coating layer leading to exposure of the hydrogen storage alloy may occur; if the coating layer is more than 1000 nm, the capacity of the negative electrode material may be significantly reduced.

[0022] From the perspective of taking into account both the charge-discharge cycle performance and stability of the negative electrode material, preferably, the coating layer includes LaF3.

[0023] From the viewpoint of taking into account both the rate charge and discharge performance and stability of the negative electrode material, preferably, the hydrogen storage alloy is an AB5 type hydrogen storage alloy; more preferably, in the crystal structure of the AB5 type hydrogen storage alloy, its A site contains X element, and its B site contains Ni element and Y element, wherein X is selected from lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium At least one element selected from the group consisting of tantalum (Tm), ytterbium (Yb), lutetium (Lu), calcium (Ca), strontium (Sr), scandium (Sc), yttrium (Y), titanium (Ti), zirconium (Zr) and hafnium (Hf), and Y is at least one element selected from the group consisting of manganese (Mn), cobalt (Co), vanadium (V), niobium (Nb), tantalum (Ta), chromium (Cr), molybdenum (Mo), iron (Fe), aluminum (Al), gallium (Ga), zinc (Zn), tin (Sn), indium (In), copper (Cu), silicon (Si), phosphorus (P) and boron (B). Based on existing knowledge: AB5 type hydrogen storage alloy is composed of mixed rare earth elements and nickel, has strong reducibility, is easily oxidized in air and aqueous solution to form metal oxides with poor conductivity, which reduces the electrochemical performance of the material; at the same time, during use, due to the reversible absorption and release of hydrogen, the alloy powder gradually pulverizes and separates from the current collector, causing the battery capacity to decay until it is scrapped. In the negative electrode material provided by the present invention, the coating layer can significantly inhibit the oxidation and pulverization of the hydrogen storage alloy, and it is effective to use the negative electrode material to improve the performance and life of the nickel-hydrogen battery.

[0024] From the perspective of taking into account both the low-temperature discharge characteristics and stability of the negative electrode material, preferably, the average particle size of the negative electrode material is recorded as M, the particle size not greater than 1 / 2 of the M is recorded as P, and the content of particles with a particle size below the P is not greater than 10wt% of the total negative electrode material. Based on existing knowledge: if the content of negative electrode material particles with a small particle size is reduced, the surface area of ​​the negative electrode material as a reaction area is reduced, so the low-temperature discharge characteristics of the battery are reduced, but the self-discharge of the battery can be suppressed. It was unexpectedly discovered that in order to suppress the self-discharge of the battery, the particle size distribution is adjusted so that the accumulation of particles below the particle size P is not greater than 10%, and the low-temperature discharge characteristics are improved at the same time.

[0025] In addition, the present invention also provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:

[0026] The step of dissolving polyvinyl pyrrolidone (PVP) in deionized water to obtain a first solution;

[0027] A step of dissolving a salt containing an Ln element in a first solution to obtain a second solution;

[0028] The step of pre-dissolving an inorganic fluoride salt with deionized water to obtain a third solution;

[0029] The step of immersing the hydrogen storage alloy in a second solution to obtain a first mixture;

[0030] The step of adding a third solution to the first mixture to obtain a second mixture;

[0031] The step of heating the second mixture to obtain a powder;

[0032] The powder is dried and then calcined.

[0033] In the preparation method provided by the present invention, the content of the coating layer in the negative electrode material is regulated by adjusting the ratio of the addition amounts of the hydrogen storage alloy, the salt containing the Ln element and NH4F.

[0034] Preferably, the inorganic fluoride salt is NH4F or NaF.

[0035] In addition, the present invention also provides a nickel-hydrogen secondary battery, which comprises a container, an electrode group contained in the container in a sealed state together with an alkaline electrolyte, the electrode group is composed of a positive electrode and a negative electrode stacked with a separator, and the negative electrode contains the above-mentioned negative electrode material. The nickel-hydrogen secondary battery is a button battery, a soft pack battery, a cylindrical battery or a square battery.

[0036] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0037] 1. In the negative electrode material, the coating layer uniformly coats the hydrogen storage alloy and the interface between the coating layer and the hydrogen storage alloy is tightly connected, thereby inhibiting the separation and splitting of the coating layer and the hydrogen storage alloy during the charge and discharge process;

[0038] 2. By including this negative electrode material in the negative electrode of the nickel-hydrogen secondary battery, the high temperature stability, low temperature discharge characteristics, charge and discharge cycle performance and rate charge and discharge performance of this nickel-hydrogen secondary battery are improved;

[0039] 3. For hydrogen storage alloys, one of the most common capacity degradation mechanisms is the passivation / corrosion of hydrogen storage alloys in alkaline electrolytes, and high temperature environments will accelerate this reaction, causing the battery to fail prematurely. The passivation products (metal oxides or hydroxides) of hydrogen storage alloys will hinder electrochemical reactions, and the elements dissolved by hydrogen storage alloys in alkaline electrolytes (such as Al, Mn, and Co, etc.) will also cause the following adverse effects: deterioration of the performance of the hydrogen storage alloy; to the surface of the positive electrode nickel hydroxide particles and cause the conductive layer (including cobalt hydroxide oxide) on the surface of the nickel hydroxide particles to degrade, thereby contaminating the nickel hydroxide particles and converting β-Ni(OH)2 into irreversible γ-NiOOH / α-Ni(OH)2; deposition in the diaphragm to cause micro-short circuits. The negative electrode material provided by the present invention can protect the hydrogen storage alloy from passivation and corrosion during cycling and high-temperature storage by forming a corrosion-resistant coating on the surface of the hydrogen storage alloy. The rare earth fluoride contained in the coating also increases the specific surface area, which is beneficial to prevent pulverization (improved capacity retention after cycling) and hydrogen adsorption (improved rate charge and discharge performance). BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings further illustrate the present invention, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention.

[0041] Figure 1 is the transmission electron microscope (TEM) image of the hydrogen storage alloy;

[0042] Figure 2 is the scanning electron microscope (SEM) image of the hydrogen storage alloy;

[0043] Figure 3 is the XPS spectrum of hydrogen storage alloy;

[0044] Figure 4 is a transmission electron microscope (TEM) image of the negative electrode material in Example 1;

[0045] Figure 5 is a transmission electron microscope (TEM) image of the negative electrode material in Example 2;

[0046] Figure 6 is a scanning electron microscope (SEM) image of the negative electrode material in Example 2;

[0047] Figure 7This is the XPS spectrum of the negative electrode material in Example 2;

[0048] Figure 8 This is a charge and discharge cycle test diagram under room temperature;

[0049] Fig. 9 This is a rate discharge test diagram under room temperature (the solid line portion in the figure is the rate discharge of the half-cell when the negative electrode material shows the highest capacity, and the dotted line portion is the rate discharge test of the half-cell after 50 charge and discharge cycles). DETAILED DESCRIPTION

[0050] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.

[0051] The nickel-hydrogen secondary battery of the present invention will now be described. The nickel-hydrogen secondary battery to which the present invention is applicable is not particularly limited.

[0052] In one embodiment, the nickel-hydrogen secondary battery has an outer can with an open top and a bottomed cylindrical shape as a container. The outer can is conductive, and its bottom wall serves as a negative terminal. A sealing body is fixed to the opening of the outer can. The sealing body includes a cover plate and a positive terminal, and provides a positive terminal while sealing the outer can. The cover plate is a conductive disc-shaped component. A cover plate and an annular insulating gasket surrounding the cover plate are arranged in the opening of the outer can, and the insulating gasket is fixed to the opening edge of the outer can by caulking the opening edge of the outer can. That is, the cover plate and the insulating gasket cooperate with each other to hermetically seal the opening of the outer can. The outer can contains an alkaline electrolyte and an electrode group. The electrode group is composed of a positive electrode, a negative electrode and a separator, which are respectively in the form of a strip, and they are wound into a spiral shape with a separator sandwiched between the positive electrode and the negative electrode. That is, the positive electrode and the negative electrode are superimposed on each other with the separator separated. The outermost periphery of the electrode group is formed by a portion of the negative electrode (the outermost portion) and contacts the inner circumferential wall of the outer can. That is, the negative electrode and the outer can are electrically connected to each other. Moreover, inside the outer can, a positive electrode pin is arranged between the electrode group and the cover plate. Specifically, one end of the positive electrode pin is connected to the positive electrode, and the other end is connected to the cover plate. Therefore, the positive terminal and the positive electrode are electrically connected to each other through the positive electrode pin and the cover plate. In addition, a circular upper insulating member is arranged between the cover plate and the electrode group, and the positive electrode pin extends through a slit provided in the upper insulating member. In addition, a circular lower insulating member is also arranged between the electrode group and the bottom of the outer can.

[0053] In one embodiment, the nickel-hydrogen secondary battery includes an alkaline electrolyte containing NaOH as a main solute, and most of the alkaline electrolyte is retained in the electrode group of the nickel-hydrogen secondary battery, so that the charge and discharge reaction is carried out between the positive electrode and the negative electrode. The alkaline electrolyte containing NaOH as the main solute may contain at least one of KOH and LiOH in addition to NaOH. Here, in the case of containing KOH and LiOH as solutes of the alkaline electrolyte, the amount of NaOH is greater than the amount of these KOH and LiOH. The self-discharge of the battery using the alkaline electrolyte with NaOH as the main body is suppressed.

[0054] In one embodiment, the separator included in the nickel-hydrogen secondary battery uses a material obtained by giving hydrophilic functional groups to a non-woven fabric made of polyamide fiber, a non-woven fabric made of polyolefin fiber such as polyethylene or polypropylene. Specifically, it is preferred to use a non-woven fabric composed of polyolefin fiber to which a sulfone group is given by sulfonation. Here, the sulfone group is given by treating the non-woven fabric with an acid containing a sulfuric acid group such as sulfuric acid or fuming sulfuric acid. If the separator is sulfonated in this way, it can not only be given hydrophilicity, but also can play an effect of suppressing the self-discharge of the battery.

[0055] In one embodiment, the positive electrode of the nickel-hydrogen secondary battery is composed of a conductive positive electrode substrate having a large number of pores forming a porous structure, and a positive electrode mixture maintained in the pores and on the surface of the positive electrode substrate. As such a positive electrode substrate, for example, a mesh, sponge or fibrous metal body or foamed nickel (nickel foam) plated with nickel can be used. The positive electrode mixture contains positive electrode active material particles, a conductive material, a positive electrode additive and a binder. The binder not only bonds the positive electrode active material particles, the conductive material and the positive electrode additive, but also serves to bond the positive electrode mixture to the positive electrode substrate. Here, as a binder, for example, carboxymethyl cellulose, methyl cellulose, PTFE (polytetrafluoroethylene) dispersion, HPC (hydroxypropyl cellulose) dispersion, etc. can be used. The positive electrode active material particles are nickel hydroxide particles or high-price nickel hydroxide particles. In addition, it is preferred that at least one of zinc, magnesium and cobalt is also dissolved in these nickel hydroxide particles. As a conductive material, for example, one or more of cobalt compounds such as cobalt oxides and cobalt hydroxides and cobalt can be used. The conductive material is added to the positive electrode mixture as needed, and the added form can be included in the positive electrode mixture in the form of a coating covering the surface of the positive electrode active material in addition to the powder form. In order to improve the characteristics of the positive electrode, the positive electrode additive is appropriately selected and added as needed. As the main positive electrode additive, yttrium oxide, zinc oxide and scandium oxide can be cited.

[0056] In one embodiment, the negative electrode of the nickel-hydrogen secondary battery is a conductive negative electrode core formed into a strip shape, in which a negative electrode mixture is retained. The negative electrode core can be made of a sheet metal material with through holes distributed therein, such as a punched metal. The negative electrode mixture is not only filled in the through holes of the negative electrode core, but also forms a layer and is retained on both sides of the negative electrode core. The negative electrode mixture contains the negative electrode material, conductive material and adhesive provided by the present invention. In addition, negative electrode additives can also be added as needed. The adhesive not only bonds the negative electrode material and conductive material provided by the present invention to each other, but also serves to bond the negative electrode mixture to the negative electrode core. Here, as a binder, a hydrophilic or hydrophobic polymer or the like can be used, and as a conductive material, carbon black, graphite, nickel powder, etc. can be used.

[0057] The negative electrode material provided by the present invention includes a hydrogen storage alloy and a coating layer arranged on the surface of the hydrogen storage alloy. The hydrogen storage alloy is not particularly limited, and an AB5 type hydrogen storage alloy is preferably used. Specifically, an AB5 type hydrogen storage alloy is preferably used, which has a crystal structure in which the A site contains an X element, and the B site contains a Ni element and a Y element, wherein X is at least one element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ca, Sr, Sc, Y, Ti, Zr and Hf, and Y is at least one element selected from Mn, Co, V, Nb, Ta, Cr, Mo, Fe, Al, Ga, Zn, Sn, In, Cu, Si, P and B. Further, in order to make the cycle life characteristics of the nickel-hydrogen secondary battery good, Y is preferably selected from Al and Mn.

[0058] The AB5 type hydrogen storage alloy can be obtained by, for example, the following method: first, weighing and mixing metal raw materials under conditions of forming a specified composition, melting the mixture in an inert gas atmosphere using, for example, a high-frequency induction melting furnace, and cooling to form an ingot; subjecting the obtained ingot to a heat treatment of heating and maintaining it at 900-1200° C. in an inert gas atmosphere for 5-24 hours; then, mechanically pulverizing the ingot cooled to room temperature to obtain a hydrogen storage alloy composed of an aggregate of hydrogen storage alloy particles. The particle size distribution state of the hydrogen storage alloy can be adjusted by adjusting the conditions of the pulverization method.

[0059] It should be noted that the XPS analysis using Thermo K-Alpha XPS described in the following implementation includes the following steps:

[0060] -Fill the holes with an appropriate amount of sample powder to make the surface of the sample holder relatively smooth;

[0061] - Place the sample holder on the load lock and pump down for 30 minutes;

[0062] - Transfer the sample holder from the load lock to the analysis chamber at a pressure below 4x10 -7 mbar;

[0063] - Fine-tune the X, Y, and Z focus positions before running an XPS experiment;

[0064] -Select La, Ni and F to perform high-resolution specific element scanning;

[0065] -Data were exported and processed using Thermo Avantage software.

[0066] [Comparative Example 1]

[0067] This comparative example provides a nickel-hydrogen secondary battery, and the preparation of the nickel-hydrogen secondary battery includes the following steps:

[0068] 1. Preparation of positive electrode

[0069] 100 parts by mass of positive electrode active material powder (1.0 parts by mass of conductive layer in positive electrode active material powder) consisting of nickel hydroxide particles (the surface of the nickel hydroxide particles has a conductive layer consisting of highly conductive cobalt hydroxide oxide), further mixed with 0.5 parts by mass of zinc oxide, 0.5 parts by mass of yttrium oxide, and 40 parts by mass of HPC dispersion, a positive electrode mixture slurry is prepared, and the positive electrode mixture slurry is filled into a sheet of nickel foam as a positive electrode substrate. After drying the nickel foam holding the positive electrode mixture, roll pressing is performed. After calendering, the nickel foam holding the positive electrode mixture is cut into a specified shape. Thereby, a positive electrode for AA size is obtained.

[0070] 2. Preparation of hydrogen storage alloy

[0071] The hydrogen storage alloy is an AB5 type hydrogen storage alloy, specifically La 9.2 Ce 6.0 Pr 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6. The raw materials containing La, Ce, Pr, Nd, Ni, Mn and Al respectively are prepared into a mixture in proportion, and the obtained mixture is melted in an argon atmosphere by a high-frequency induction melting furnace. The molten metal is poured into a casting mold and cooled to room temperature to obtain an ingot of a hydrogen storage alloy. Then, the ingot is subjected to heat treatment. The conditions of the heat treatment are to heat the ingot to 1080°C in a tubular furnace in an argon atmosphere and keep it for 5 hours to obtain better uniformity. Then, after the heat treatment, the ingot of the hydrogen storage alloy is cooled to room temperature. Then, the ingot of the hydrogen storage alloy is mechanically crushed by a crusher in an argon atmosphere, and a powder composed of hydrogen storage alloy particles is obtained by passing through a 200-mesh sieve. Here, the powder is analyzed by a transmission electron microscope (TEM), and the results are as follows. Figure 1 The powder was analyzed by scanning electron microscope (SEM), and the results were as follows: Figure 2 The powder was analyzed by XPS using Thermo K-Alpha XPS, and the results were as follows Figure 3 shown.

[0072] 3. Preparation of negative electrode

[0073] With respect to 100 parts by mass of the obtained hydrogen storage alloy, 0.4 parts by mass of sodium polyacrylate, 0.1 parts by mass of carboxymethyl cellulose, 2.5 parts by mass of styrene butadiene copolymer, 1.0 parts by mass of carbon black and 30 parts by mass of water were added and kneaded to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was evenly and fixedly applied to both sides of an iron perforated plate serving as a negative electrode core. In addition, the perforated plate had a thickness of 40 μm and was nickel-plated on its surface. After the slurry was dried, the perforated plate holding the negative electrode mixture containing the powder of the hydrogen storage alloy was further rolled to increase the amount of alloy per unit volume, and then cut to produce an AA-size negative electrode containing the hydrogen storage alloy.

[0074] 4. Assembly of NiMH secondary batteries

[0075] The positive electrode and the negative electrode are wound into a spiral shape in a state where the separator is sandwiched between the obtained positive electrode and the negative electrode to produce an electrode group. The separator used in the production of the electrode group here is formed by a non-woven fabric made of polypropylene fiber obtained by sulfonation treatment. The above-mentioned electrode group is contained in an outer can with a bottom cylindrical shape, and 2.2g of the alkaline electrolyte (alkaline electrolyte containing KOH, NaOH and LiOH) is injected. Then, the opening of the outer can is plugged with a sealing body and assembled into a nickel-hydrogen secondary battery of AA size with a nominal capacity of 2500mAh.

[0076] 5. Initial activation treatment

[0077] The obtained battery was charged at a current of 0.1 C for 16 hours at a temperature of 25° C., and then discharged at a current of 0.2 C until the battery voltage reached 0.5 V. This initial activation treatment was repeated twice. At this point, the nickel-hydrogen secondary battery was ready for use.

[0078] [Comparative Example 2]

[0079] This comparative example provides a half-cell that can be applied to electrochemical performance testing. The preparation of the half-cell includes the following steps:

[0080] 1. Negative electrode preparation

[0081] Take 40 mg of negative electrode material and 160 mg of nickel powder and mix them evenly to form a mixture. The mixture is transferred to a mold and pressed into a cake-shaped negative electrode (thickness of 10 mm) on a fully automatic tablet press. The parameters set for the fully automatic tablet press are: upper pressure limit 3.0 t, lower pressure limit 2.7 t, pressurization time 1 min, and mold diameter 10 mm.

[0082] 2. Cathode production

[0083] A commercially available sintered positive electrode that is matched to the negative electrode and suitable for preparing a half-cell is used.

[0084] 3. Assembly of half-cell

[0085] Take a diaphragm (the diaphragm is composed of laminated grafted polypropylene and polyethylene) and fold it in half to clamp the negative electrode, so that each side of the negative electrode is in contact with the diaphragm. Then take two sintered positive electrodes (the two sintered positive electrodes are connected by a nickel sheet), and clamp the negative electrode wrapped by the diaphragm with the two sintered positive electrodes to form an electrode assembly. Place the electrode assembly into an acrylic battery holder, and then place the acrylic battery holder containing the electrode assembly in a 100 ml container, and then soak the acrylic battery holder with a 30wt% KOH solution to obtain a half-cell in a flooded state.

[0086] 4. Half-battery test

[0087] The sintered positive electrode was used as the counter electrode and reference electrode, and the prepared negative electrode was used as the working electrode to conduct electrochemical tests on the working electrode. Two cycles of activation treatment were performed before the test, specifically: Step 1, the half-cell was charged at a current density of 100mA / g for 5h; Step 2, after charging, the half-cell was discharged at a current density of 100mA / g until it reached a cut-off voltage of 0.9V; Step 3, the half-cell was discharged at a current density of 24mA / g until it reached a cut-off voltage of 0.9V.

[0088] It should be noted that the negative electrode material used in this comparative example is the hydrogen storage alloy in comparative example 1, namely La 9.2 Ce6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 .

[0089] [Comparative Example 3]

[0090] This comparative example provides a half-cell that can be used for electrochemical performance testing. The only difference between the half-cell provided in this comparative example and the half-cell provided in comparative example 2 is that the negative electrode material used in the half-cell of this comparative example includes: the hydrogen storage alloy in comparative example 1 and a nickel coating layer arranged on the surface of the hydrogen storage alloy.

[0091] The preparation of the negative electrode material of this comparative example includes the following steps:

[0092] Step 1, placing the hydrogen storage alloy into solution I (comprising 0.05 mol / L NiSO4 and 0.05 mol / L N2H4·H2SO4) and stirring for 5 minutes;

[0093] Step 2, adding solution II (comprising 0.64 g / L NaBH4 and 0.2 g / L NaOH) into solution I, and stirring for 20 minutes to obtain a mixture;

[0094] Step three, separating the mixture into solid and liquid, and vacuum drying the collected solid particles at 60° C. to obtain the negative electrode material.

[0095] [Comparative Example 4]

[0096] This comparative example provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this comparative example and the half-cell provided in comparative example 2 is that the negative electrode material used in the half-cell of this comparative example is a hydrogen storage alloy (La 9.2 Ce 6.0 Pr 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ).

[0097] The preparation of the negative electrode material of this comparative example includes the following steps:

[0098] Step 1, immersing the hydrogen storage alloy in a solution containing KF and HF at 50° C., and then adding KBH4 into the solution;

[0099] Step 2: The fluorination treatment is considered complete until the hydrogen bubbles disappear;

[0100] Step 3: The hydrogen storage alloy after fluorination treatment is washed in distilled water and ethanol, and then dried in a vacuum at 50° C. to obtain a negative electrode material.

[0101] [Example 1]

[0102] This embodiment provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this embodiment and the half-cell provided in Comparative Example 2 is that the negative electrode material used in this embodiment includes a hydrogen storage alloy (La 9.2 Ce 6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ) and a LaF3 coating layer disposed on the surface of the hydrogen storage alloy, the coating layer having a content of 2wt% based on the mass of the negative electrode material. Here, the negative electrode material used in this embodiment is analyzed using a transmission electron microscope (TEM), and the results obtained are as follows: Figure 4 shown.

[0103] The preparation of the negative electrode material of this embodiment includes the following steps:

[0104] Step 1, weighing hydrogen storage alloy, polyvinyl pyrrolidone PVP (MV is about 55000), La(NO3)3·6H2O (MV is 433.01 g / mol) and NH4F (MV is 37.04 g / mol). It should be noted that every 1 g of hydrogen storage alloy corresponds to 0.01 g of PVP, 0.04421 g of La(NO3)3·6H2O and 0.01134 g of NH4F;

[0105] Step 2: In a reaction container, PVP is dissolved in deionized water (every 0.01 g of PVP corresponds to 10 mL of deionized water), and stirred at a stirring speed of 500 RPM for 10 minutes to obtain a first solution.

[0106] Step 3, using the first solution to dissolve La(NO3)3·6H2O to obtain a second solution;

[0107] Step 4, dissolving NH4F in deionized water (every 0.01134 g of NH4F corresponds to 1 mL of deionized water) to obtain a third solution;

[0108] Step 5, heating the second solution in the reaction container to 80° C., setting the stirring speed to 300 RPM, and immersing the hydrogen storage alloy in the reaction container to obtain a first mixture;

[0109] Step six, adding the third solution dropwise to the first mixture into the second mixture using a pipette;

[0110] Step 7, continuously stirring and heating the second mixture at 80° C. until the solution is completely evaporated to obtain a powder;

[0111] Step eight, drying the obtained powder in a vacuum oven at 80° C. for 12 hours, and then calcining it in an argon environment at 100° C. for 1 hour to obtain a negative electrode material.

[0112] [Example 2]

[0113] This embodiment provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this embodiment and the half-cell provided in Example 1 is that the negative electrode material used in this embodiment includes a hydrogen storage alloy (La 9.2 Ce 6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ) and a LaF3 coating layer disposed on the surface of the hydrogen storage alloy, the coating layer having a content of 4wt% based on the mass of the negative electrode material. Here, the negative electrode material used in this embodiment is analyzed using a transmission electron microscope (TEM), and the results obtained are as follows: Figure 5 The negative electrode material used in this embodiment was analyzed by scanning electron microscope (SEM), and the results obtained are as follows Figure 6 Thermo K-Alpha XPS was used to perform XPS analysis on the negative electrode material used in this embodiment, and the results obtained were as shown Figure 7 shown.

[0114] Depend on Figure 1 , Figure 4 and Figure 5 By comparison, it can be seen that the coating layer of the negative electrode material provided by the present invention uniformly coats the hydrogen storage alloy. Figure 6 and Figure 2 By comparison, it can be seen that compared with the surface of the bare hydrogen storage alloy particles, the surface of the negative electrode material provided with the LaF3 coating layer is rougher, or in other words, has a larger specific surface area. Figure 3 and Figure 7 By comparison, it can be seen that the exposed hydrogen storage alloy does not contain the F element, while the F element in the negative electrode material provided by the present invention is located on the surface of the hydrogen storage alloy.

[0115] The preparation method of the negative electrode material in this embodiment is different from that in Embodiment 1 only in that every 1 g of hydrogen storage alloy corresponds to 0.01 g of PVP, 0.08840 g of La(NO3)3·6H2O and 0.02238 g of NH4F.

[0116] [Example 3]

[0117] This embodiment provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this embodiment and the half-cell provided in Example 1 is that the negative electrode material used in this embodiment includes a hydrogen storage alloy (La 9.2 Ce 6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ) and an ErF3 coating layer disposed on the surface of the hydrogen storage alloy, wherein the content of the coating layer is 3wt% based on the mass of the negative electrode material.

[0118] The preparation method of the negative electrode material in this embodiment is different from that in Embodiment 1 only in that every 1 g of hydrogen storage alloy corresponds to 0.01 g of PVP, 0.05930 g of Er(NO3)3·5H2O (MV is 443.35 g / mol) and 0.01486 g of NH4F.

[0119] [Example 4]

[0120] This embodiment provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this embodiment and the half-cell provided in Example 1 is that the negative electrode material used in this embodiment includes a hydrogen storage alloy (La 9.2 Ce 6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ) and a NdF3 coating layer disposed on the surface of the hydrogen storage alloy, wherein the content of the coating layer is 2.5wt% based on the mass of the negative electrode material.

[0121] The preparation of the negative electrode material of this embodiment includes the following steps:

[0122] Step 1, weighing hydrogen storage alloy, polyvinyl pyrrolidone PVP (MV is about 55000), NdCl3·6H2O (MV is 358.69 g / mol) and NaF. It should be noted that every 1g of hydrogen storage alloy corresponds to 0.01g of PVP and 0.04456g of NdCl3·6H2O;

[0123] Step 2: In a reaction container, PVP is dissolved in deionized water (every 0.01 g of PVP corresponds to 10 mL of deionized water), and stirred at a stirring speed of 500 RPM for 10 minutes to obtain a first solution.

[0124] Step 3, using the first solution to dissolve NdCl3·6H2O to obtain a second solution;

[0125] Step 4, dissolving NaF in deionized water to obtain a third solution. Specifically, the third solution is a 0.5 M NaF solution, and 1 g of the hydrogen storage alloy corresponds to 0.745 mL of the third solution;

[0126] Step 5, heating the second solution in the reaction container to 75° C., setting the stirring speed to 300 RPM, and immersing the hydrogen storage alloy in the reaction container to obtain a first mixture;

[0127] Step six, adding the third solution dropwise to the first mixture into the second mixture using a pipette;

[0128] Step 7, the second mixture is heated at 75° C. for 2 hours under continuous stirring to obtain a suspension, the suspension is centrifuged to obtain a separated powder solid, and the powder solid is washed three times with deionized water;

[0129] Step eight, drying the cleaned powder in a vacuum oven at 80° C. for 12 hours, and then calcining in an argon environment at 100° C. for 1 hour to obtain a negative electrode material.

[0130] [Example 5]

[0131] This embodiment provides a half-cell that can be used for electrochemical performance testing. The difference between the half-cell provided in this embodiment and the half-cell provided in Example 1 is that the negative electrode material used in this embodiment includes a hydrogen storage alloy (La 9.2 Ce 6. 0P 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 ) and a YbF3 coating layer disposed on the surface of the hydrogen storage alloy, wherein the content of the coating layer is 3.5wt% based on the mass of the negative electrode material.

[0132] The preparation method of the negative electrode material in this embodiment differs from that in Embodiment 1 only in that every 1 g of hydrogen storage alloy corresponds to 0.01 g of PVP, 0.06833 g of Yb(NO3)3·5H2O (MV is 449.13 g / mol) and 0.01691 g of NH4F.

[0133] [Example 6]

[0134] A nickel-hydrogen secondary battery was produced in the same manner as in Comparative Example 1, except that the surface of the hydrogen storage alloy was coated with a LaF 3 coating layer (the mass ratio of the hydrogen storage alloy surface to the coating layer was 49:1).

[0135] [Example 7]

[0136] A nickel-hydrogen secondary battery was produced in the same manner as in Comparative Example 1, except that the surface of the hydrogen storage alloy was coated with a LaF 3 coating layer (the mass ratio of the hydrogen storage alloy surface to the coating layer was 24:1).

[0137] [Example 8]

[0138] A nickel-hydrogen secondary battery was produced in the same manner as in Comparative Example 1, except that the surface of the hydrogen storage alloy was coated with a NdF 3 coating layer (the mass ratio of the hydrogen storage alloy surface to the coating layer was 39:1).

[0139] [Example 9]

[0140] A nickel-hydrogen secondary battery was produced in the same manner as in Comparative Example 1, except that the surface of the hydrogen storage alloy was coated with a YbF 3 coating layer (the mass ratio of the hydrogen storage alloy surface to the coating layer was 96.5:3.5).

[0141] The following tests were performed on the half-cell provided in Comparative Example 2 and the half-cell provided in Examples 1-2, and the tester was LANHE CT2001A.

[0142] [Room temperature charge and discharge cycle and rate discharge test]

[0143] The test steps include:

[0144] - The half-cell was charged at a current density of 300 mA / g for 100 min;

[0145] - The half-cell was discharged at a current density of 900 mA / g until a cut-off voltage of 0.9 V was reached;

[0146] - The half-cell was discharged at a current density of 600 mA / g until a cut-off voltage of 0.9 V was reached;

[0147] - The half-cell was discharged at a current density of 300 mA / g until a cut-off voltage of 0.9 V was reached;

[0148] - The half-cell was discharged at a current density of 200 mA / g until a cut-off voltage of 0.9 V was reached;

[0149] - The half-cell was discharged at a current density of 100 mA / g until a cut-off voltage of 0.9 V was reached;

[0150] - The half-cell was discharged at a current density of 60 mA / g until a cut-off voltage of 0.9 V was reached

[0151] - Cycle the charge and discharge steps 50 times.

[0152] The cycle test results are as follows Figure 8 As shown, the test results show that the half-cell of Example 2 performs best, and the half-cell of Comparative Example 2 performs worst, indicating that the negative electrode material provided by the present invention can significantly improve the room temperature cycle stability, and the improvement effect is positively correlated with the content of the coating layer in the negative electrode material. However, at the same time, the negative electrode material provided by the present invention inevitably sacrifices capacity due to the coating layer, so it is reasonable to set the content of the coating layer in the negative electrode material to 2-4wt%.

[0153] The rate discharge test results are as follows: Fig. 9 As shown, the test results show that: after the half-cell has been charged and discharged for 50 cycles, the rate discharge performance is improved; after the half-cells of Examples 1-2 have been charged and discharged for 50 cycles, the capacity remains unchanged when discharged at the highest rate; but after the half-cells of Comparative Example 2 have been charged and discharged for 50 cycles, the capacity decreases when discharged at the highest rate; the negative electrode material provided by the present invention has improved rate performance, specifically, the battery can still maintain stable capacity at a high rate after multiple charge and discharge cycles in a high temperature environment.

[0154] The half-cell provided in Comparative Example 3, the half-cell provided in Comparative Example 4, and the half-cell provided in Example 2 were also subjected to room temperature charge and discharge cycle tests. The test results show that nickel coating or fluorination treatment on the surface of the hydrogen storage alloy does not improve the charge and discharge cycle stability under room temperature environment. The negative electrode material provided by the present invention can significantly improve the charge and discharge cycle stability under room temperature environment.

[0155] The negative electrode material of Comparative Example 2 and the negative electrode material of Example 2 were tested as follows.

[0156] [High temperature alkali washing test]

[0157] The test steps include:

[0158] - Weigh 0.25 g of sample;

[0159] -Each sample was transferred to a 15 mL tube;

[0160] - Add 12 mL of 30 wt% KOH solution into the test tube and stir;

[0161] - Heat the test tube in a DFZ-6020 oven preheated to 100°C for 4 hours;

[0162] -After 4 hours, remove the tube from the oven and cool to room temperature;

[0163] -Take 10 mL of the upper layer of the suspension in the test tube for ICP analysis.

[0164] The test results are shown in Table 1. The Al and Mn detected in the separated solution are precipitated from the hydrogen storage alloy in the high-temperature alkaline solution. Therefore, the lower the traces of Al and Mn detected in the separated solution, the better the stability of the negative electrode material at high temperature. Therefore, the coating layer of the negative electrode material provided by the present invention can significantly inhibit the precipitation of Al and Mn from the hydrogen storage alloy in the high-temperature alkaline solution, and has excellent high-temperature stability.

[0165] Table 1

[0166]

[0167] [High temperature electrochemical test]

[0168] The test steps include:

[0169] - After half-cell activation, charge at a current density of 100 mA / g for 5 hours;

[0170] - Place the half-cell in a DFZ-6020 oven set at 50°C;

[0171] - Half battery rests for 72 hours;

[0172] - Remove the half-cell from the oven and cool to room temperature;

[0173] - The remaining half-cell power is discharged at a current density of 100 mA / g until a cut-off voltage of 0.9 V is reached;

[0174] - The half-cell was charged at a current density of 100 mA / g for 5 h;

[0175] - The half-cell was discharged at a current density of 100 mA / g until a cut-off voltage of 0.9 V was reached

[0176] - Repeat the above steps.

[0177] The high temperature electrochemical test results are shown in Table 2. The test results show that the coating layer of the negative electrode material provided by the present invention can significantly improve the capacity recovery after high temperature placement and has excellent high temperature stability.

[0178] Table 2

[0179] Comparative Example 2 Example 2 Original room temperature capacity 100% 100% After being placed in high temperature once, the room temperature capacity 88% 96% After being placed in high temperature twice, the room temperature capacity 86% 96%

[0180] In addition, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible. For example, the nickel-hydrogen secondary battery may be a square battery, and there is no particular limitation on the mechanical structure.

[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0182] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a negative electrode material, characterized in that: The negative electrode material includes a hydrogen storage alloy and a coating layer arranged on the surface of the hydrogen storage alloy; Based on the mass of the negative electrode material, the content of the coating layer is 2-4wt%; The coating layer includes LaF3; The method comprises the following steps: The step of dissolving polyvinyl pyrrolidone in deionized water to obtain a first solution; A step of dissolving a salt containing La element in a first solution to obtain a second solution; The step of pre-dissolving an inorganic fluoride salt with deionized water to obtain a third solution; The step of immersing the hydrogen storage alloy in a second solution to obtain a first mixture; The step of adding a third solution to the first mixture to obtain a second mixture; The step of heating the second mixture to obtain a powder; The powder is dried and then calcined.

2. The method according to claim 1, characterized in that The coating layer also includes the general formula LnF x In the components shown, Ln is an element selected from Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y and Sc.

3. The method according to claim 1, characterized in that: The hydrogen storage alloy is an AB5 type hydrogen storage alloy. In the crystal structure of the hydrogen storage alloy, the A site contains the X element, and the B site contains the Ni element and the Y element. X is at least one element selected from La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ca, Sr, Sc, Y, Ti, Zr and Hf, and Y is at least one element selected from Mn, Co, V, Nb, Ta, Cr, Mo, Fe, Al, Ga, Zn, Sn, In, Cu, Si, P and B.

4. The method according to claim 1, characterized in that: The hydrogen storage alloy is La 9.2 Ce 6.0 Pr 0.2 Nd 0.7 Zr 0.3 Ni 73.0 Mn 5.9 Al 4.6 .

5. The method according to claim 1, characterized in that The coating layer has a thickness of 0.1-1000 nm.

6. The method according to claim 1, characterized in that The inorganic fluoride salt is NH4F or NaF.

7. A nickel-hydrogen secondary battery, characterized in that A container is provided, and an electrode group is contained in the container in a sealed state together with an alkaline electrolyte, the electrode group is composed of a positive electrode and a negative electrode stacked with a separator therebetween, and the negative electrode contains a negative electrode material prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nickel-metal hydride secondary battery cathode material

    CN104681817A

  • Method for producing slurry for negative electrode, and slurry for negative electrode

    TW202224240A